The broad spectrum of cardiovascular adverse events related to immune check point inhibitors. (25th November 2020) - Andres, M.S; Baksi, J; Khattar, R; Rosen, S.D; Lyon, A.R
Abstract: Background: Immunotherapy is one of the latest and most exciting developments in cancer treatment. Immune checkpoint inhibitors (ICI) have shown to have impressive positive results on several tumours such as melanoma, renal cancer and lung cancer, among others. Along with its benefits come the adverse effects which, concerning the heart, myocarditis is the most well-known and feared event. Yet, the spectrum of cardiovascular adverse events (CVAE) is much broader, ranging from heart failure to arrhythmias, but this has not been well documented until know. Objective: Describe the broad spectrum of CVAE related to ICI Methods: Observational retrospective, single centre study. We evaluated all the patients that have been referred to the cardio oncology (CO) unit and were under ICI treatment. The referred patients underwent a day case assessment with cardiovascular tests (blood tests, ECG, resting echocardiogram in all cases and MRI, stress echo or CT coronary angiogram if needed). The results were discussed in the multidisciplinary team meeting and the patients were then reviewed by one of the doctors in the team. The conclusions of the assessment were then communicated to the oncology team. Results: From the year 2011 until December 2019, 71 patients receiving immunotherapy were referred to the CO unit. Three patients were excluded because they were referred for having an intracardiac tumour, leaving 68 for analysis. The first patient was referred in 2014 and during the first 3 years only 7 patients were reviewed in the CO unit. The frequency increased dramatically in 2017 to 17, 19 in 2018 and 25 in 2019. 21 patients were receiving Nivolumab, 24 on Ipilimumab, and 23 (34%) on combined therapy. The most frequent tumour was Melanoma (26/68, 38%). Regarding the CVAE: 22 patients (32%) were referred for investigtion of myocarditis. 6 had a diagnosis of definite myocarditis, 5 probable and 4 possible. Other CVAE (20/68, 29%) were the supraventricular arrhythmias including atrial fibrilation (20/68, 29%). 8 patients presented with non-inflammatory heart failure with new LVEF drop, 4 with chest pain, and 4 others with syncope. 1 patient developed pulmonary hypertension. Conclusions: Myocarditis still remains the most frequent CVAE related to ICI, but the spectrum is broader than initially described. Supraventricular arrhythmias and non-inflammatory LVEF disfunction were very frequent in this series and we suspect that the incidence will increase as cardiologist and oncologists start considering them as probable adverse effects of this treatment. Funding Acknowledgement: Type of funding source: None